2010
DOI: 10.2466/pms.110.1.61-68
|View full text |Cite
|
Sign up to set email alerts
|

Bench Press Training Program with Attached Chains for Female Volleyball and Basketball Athletes

Abstract: Attaching chains to barbells to increase strength and power has become popular for athletes; however, little scientific evidence supports this practice. The present purpose was to compare chain training to traditional training for the bench press. Women collegiate athletes in volleyball and basketball (N = 19) participated in a 16-session bench press program. They were matched into either a Traditional or a Chain training group by 1-repetition maximum (1RM). The Traditional group performed the bench press with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
2
4
0
2
Order By: Relevance
“…A total of 22 reports that comprised both trained and untrained participants were included for the meta-analysis [ 8 , 16 , 22 , 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. As shown in Figure 2 , VRT and CRT significantly differed in the improvement of the maximum strength of the subjects (ES = 0.80; 95% CI: 0.42–1.19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 22 reports that comprised both trained and untrained participants were included for the meta-analysis [ 8 , 16 , 22 , 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. As shown in Figure 2 , VRT and CRT significantly differed in the improvement of the maximum strength of the subjects (ES = 0.80; 95% CI: 0.42–1.19).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis conducted on the studies of only trained subjects showed that VRT favored a significantly higher improvement of maximum strength than CRT (ES = 0.57; 95% CI: 0.22–0.93; Figure 3 ) [ 8 , 22 , 23 , 24 , 32 , 36 , 37 , 38 , 39 ]. Based on the VRT workload, we then subgrouped the studies into <80% and ≥80% 1RM.…”
Section: Resultsmentioning
confidence: 99%
“…Adicionalmente, o primeiro estudo que envolveu treinamento com uso de correntes por oito semanas com atletas pode notar melhoras decorrentes deste método de treino, devido ao aumento da velocidade da barra no PFM, o que poderia recrutar maior quantidade de fibras do tipo IIb e incrementar a produção de força subsequente. (BURNHAM; RUUD; MCGOWAN, 2010).…”
Section: Resultsunclassified
“…E, recentemente, observou-se que esta estratégia também é adequada para o aumento da força no supino reto entre atletas de voleibol e basquetebol. (BURNHAM; RUUD; MCGOWAN, 2010).…”
Section: Introductionunclassified
“…Similar findings were noted by many researchers (Kasabalis et al, 2005;Häkkinen, 1993;Marques et al, 2008;Newton et al, 2006). It has been seen that the application of the training programs using strength and power exercises would be particularly effective in improving performance (Burnham et al, 2010;Gabbett, 2008).…”
Section: Discussionmentioning
confidence: 99%